Genome-wide Ancestry and Demographic History of African-Descendant Maroon Communities from French Guiana and Suriname (2017)
The transatlantic slave trade was the largest forced migration in world history. However, the origins of the enslaved Africans and their admixture dynamics remain unclear. To investigate the demographic history of African-descendant Marron populations, we generated genome-wide data (4.3 million markers) from 107 individuals from three African-descendant populations in South America, as well as 124 individuals from six west African populations. Throughout the Americas, thousands of enslaved Africans managed to escape captivity and establish lasting communities, such as the Noir Marron. We find that this population has the highest proportion of African ancestry ( 98%) of any African-descendant population analyzed to date, presumably because of centuries of genetic isolation. By contrast, African-descendant populations in Brazil and Colombia harbor substantially more European and Native American ancestry as a result of their complex admixture histories. Using ancestry tract-length analysis, we detect different dates for the European admixture events in the African-Colombian (1749 CE; confidence interval [CI]: 1737–1764) and African-Brazilian (1796 CE; CI: 1789–1804) populations in our dataset, consistent with the historically attested earlier influx of Africans into Colombia. Furthermore, we find evidence for sex-specific admixture patterns, resulting from predominantly European paternal gene flow. Finally, we detect strong genetic links between the African-descendant populations and specific source populations in Africa on the basis of haplotype sharing patterns. Although the Noir Marron and African-Colombians show stronger affinities with African populations from the Bight of Benin and the Gold Coast, the African-Brazilian population from Rio de Janeiro has greater genetic affinity with Bantu-speaking populations from the Bight of Biafra and west central Africa.